2007
DOI: 10.1080/01926230701481923
|View full text |Cite
|
Sign up to set email alerts
|

Novel Use of Botulinum Toxin to Ameliorate Arthrofibrosis: An Experimental Study in Rabbits

Abstract: This study aimed to investigate the effects of intra-articular botulinum toxin in preventing arthrofibrosis. Arthrofibrosis was induced in both stifle joints of 20 rabbits by transecting the anterior cruciate ligament under intramuscular anesthesia with ketamine and xylazine. Intra-articular toxin at a dose of 0.6 ml (50 unit) and physiologic saline solution (0.6 ml) were injected into the right and left stifle joints, respectively, 3 times with a 1-week interval between each injection. The rabbits were euthan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 29 publications
0
15
0
1
Order By: Relevance
“…[13] Intra-articular botulinum toxin has been demonstrated to be useful in preventing arthrofibrosis in rabbits after transection of the anterior cruciate ligament. [14]…”
Section: Botulinum Toxin In Prophylactic Use For Scarsmentioning
confidence: 99%
“…[13] Intra-articular botulinum toxin has been demonstrated to be useful in preventing arthrofibrosis in rabbits after transection of the anterior cruciate ligament. [14]…”
Section: Botulinum Toxin In Prophylactic Use For Scarsmentioning
confidence: 99%
“…These results suggest that the role of BTX-A may be associated with fibrosis and inflammation. A previous study demonstrated that an intra-articular injection of BTX-A into the rabbit knee prevented adhesion formation and reduced arthrofibrosis of the knee after knee surgery [21], but the precise mechanism remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…A short course of oral steroids is more attractive than intra-articular steroids, but may not be adequate to reverse the fibroplastic process. Namazi and co-investigators have studied arthrofibrosis of the knee in New Zealand White Rabbits by dividing the anterior cruciate ligament [22]. They were able to prevent the development of intraarticular scar by injecting botulinum toxin (Botox).…”
Section: Postoperative Managementmentioning
confidence: 99%